(3GdQO GdSOjO Ydi eWGYf MSf GdeGdcj Ydi CFeI GdOYhI hebQQGJ GdJhMjO (B/s - (3GdQMjdj, EHQGgje Hf YGeQ s 1383 (3gLQj(B-s; (3GdeGdcj, MSf Hf aQMGfs 1390 (3gLQj(B-.s ((3GdeOjfI GdfHhjI (B- (3GdSYhOjI (B:s (3OGQ efGQ GdJhMjO ddfTQ,s, 2010)
(3jJfGhd GdcJGH fbO dcJGH MSf GdeGdcj GdeSei efGgL GdJYdje (B: (3bQGAI fbOjI debQQGJ GdJhMjO deQGMd GdJYdje GdYGe(B.s
Keywords: (3GdeGdcj, MSf Hf aQMGfs -- 1390 (3gLQj(B-s -- (3BQGA Mhd Yde GdcdGes; (3Yde GdcdGes -- (3OaY eWGYfs; (3GdESdGes -- (3OaGY Yf GdYbjOIs; (3QOhO hTHgGJs